Thermodynamics and symmetry of human catabiosis - the present understanding - Dutta, Ahbijit; Chattopadhyay, Himadri; Çatak, Jale; Çatak, Jale (Inderscience Publishers, 2023)
In this paper, the topic of human catabiosis has been explored from the vantage of thermodynamics. Research works on human catabiosis based on non-equilibrium thermodynamics are summarised. The origin of the human species, reproduction, growth, and ageing are reviewed from the perspective of thermodynamics, and finally, the future direction of the subject is discussed. The choice of dietary patterns and geographical locations influencing the ageing process are also discussed in this article.
Keywords: Ageing; Catabiosis; Growth; Thermodynamics